2019
DOI: 10.3390/su11071836
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Performance, Financialization, and Real Investment in US Manufacturing Firms

Abstract: In recent years, the global financial and economic crisis are rewriting the relationship between business and society, focusing, among other things, on the role of the process of financialization, not only in the economy as a whole but also within non-financial companies. Shareholder value maximization, together with the commoditization of business, has led to a general short-term approach at the expense of capital accumulation and core business activity, to the detriment of not only firms’ competitiveness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 86 publications
(139 reference statements)
0
32
0
Order By: Relevance
“…Many of the research studies carried out on CSR have found relationships between the company's social, environmental, and financial and economic performance (Brogi and Lagasio 2019;Chowdhury et al 2019;Taliento et al 2019), concluding that the three dimensions are interconnected, and joint action ensures long-term sustainability. Likewise, all of them have a bearing on the generation of value for stakeholders in the long term, on the improvement of the relationship between stakeholders and the company, and on management's control and planning mechanisms that protect stakeholders' interests and expectations (Cupertino et al 2019;Jamali 2008;Pirnea et al 2011). Through the development of CSR practices, the reconciliation of social and economic objectives and the reconciliation of the interests of the company and society are achieved (Bagire et al 2011;Degie and Kebede 2019;Park et al 2014;Saiia et al 2003).…”
Section: The Development Of Csr In the Business Worldmentioning
confidence: 99%
“…Many of the research studies carried out on CSR have found relationships between the company's social, environmental, and financial and economic performance (Brogi and Lagasio 2019;Chowdhury et al 2019;Taliento et al 2019), concluding that the three dimensions are interconnected, and joint action ensures long-term sustainability. Likewise, all of them have a bearing on the generation of value for stakeholders in the long term, on the improvement of the relationship between stakeholders and the company, and on management's control and planning mechanisms that protect stakeholders' interests and expectations (Cupertino et al 2019;Jamali 2008;Pirnea et al 2011). Through the development of CSR practices, the reconciliation of social and economic objectives and the reconciliation of the interests of the company and society are achieved (Bagire et al 2011;Degie and Kebede 2019;Park et al 2014;Saiia et al 2003).…”
Section: The Development Of Csr In the Business Worldmentioning
confidence: 99%
“…Finally, as most previous studies have suggested (e.g., Cupertino et al [96]; Masocha [97]; Xue et al [98]) the sustainability issues such as environmental, social, and governance standards, may enhance an organization's innovation and long-term growth with a positive effect on its long-term value. The next section adds to this literature by incorporating a model (i.e., throughput model) that examines sustainability issues via a process apparatus as opposed to a black box.…”
Section: Summary For Sustainability Researchmentioning
confidence: 79%
“…Li and Wu pointed that there is a performance gap of CSR engagements between stakeholders-related and shareholders-related activities [ 13 ]. The findings of Cupertino et al also found this performance gap, indicating that financialization can promote the capital accumulation of firms with some social responsibility practices [ 32 ]. Lu et al made an analysis of the impact of different dimensions of CSR on corporate competitiveness, and found that the environmental and social dimensions of CSR can be the main factors in promoting financial performance [ 33 ].…”
Section: Literature Review and Hypothesesmentioning
confidence: 96%